Modeling the thickness of perennial ice covers on stratified lakes of the Taylor Valley, Antarctica - M. K. OBRYK; P. T. DORAN; J. A. HICKS; C. P. McKAY; J. C. PRISCU (Journal of Glaciology, 2016)
A 1-D ice cover model was developed to predict and constrain drivers of long-term ice thickness trends in chemically stratified lakes of Taylor Valley, Antarctica. The model is driven by surface radiative heat fluxes and heat fluxes from the underlying water column. The model successfully reproduced 16 a (between 1996 and 2012) of ice thickness changes for the west lobe of Lake Bonney (average ice thickness = 3.53 m) and Lake Fryxell (average ice thickness = 4.22 m). Long-term ice thickness trends require coupling with the thermal structure of the water column. The heat stored within the temperature maximum of lakes exceeding a liquid water column depth of 20 m can either impede or facilitate ice thickness change depending on the predominant climatic trend (cooling or warming). As such, shallow (<20 m deep water columns) perennially ice-covered lakes without deep temperature maxima are more sensitive indicators of climate change. The long-term ice thickness trends are a result of surface energy flux and heat flux from the deep temperature maximum in the water column, the latter of which results from absorbed solar radiation.